2018
DOI: 10.3390/rs10071151
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground Forest Biomass Estimation Combining L- and P-Band SAR Acquisitions

Abstract: While considerable research has focused on using either L-band or P-band SAR (Synthetic Aperture Radar) on their own for forest biomass retrieval, the use of the two bands simultaneously to improve forest biomass retrieval remains less explored. In this paper, we make use of L- and P-band airborne SAR and in situ data measured in the field together with laser scanning data acquired over one hemi-boreal (Remningstorp) and one boreal (Krycklan) forest study area in Sweden. We fit statistical models to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…Previous studies reported that long-wavelength PolSAR data, such as the L and the P bands, are well correlated with mangrove forest structures. Among these data, crossed-polarized HV appears to be most correlated with biophysical attributes [13,66,67]. The variable-importance analysis revealed that crossed-polarization HV is more sensitive to mangrove AGB in the study area than HH polarization ( Figure 6), consistent with previous results [26,29].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies reported that long-wavelength PolSAR data, such as the L and the P bands, are well correlated with mangrove forest structures. Among these data, crossed-polarized HV appears to be most correlated with biophysical attributes [13,66,67]. The variable-importance analysis revealed that crossed-polarization HV is more sensitive to mangrove AGB in the study area than HH polarization ( Figure 6), consistent with previous results [26,29].…”
Section: Discussionsupporting
confidence: 89%
“…However, the accuracy of tree AGB estimation is relatively low, as there are problems of low image resolution, remote sensing signal response saturation, data conversion between different scales, and data heterogeneity [6]. Tree AGB estimation of a forest with Synthetic Aperture Radar (SAR) [7][8][9][10][11] and Light Detection And Ranging (LiDAR) [12][13][14][15] is of relative high accuracy, but the equipment involved is very expensive, and the data acquisition process is usually time-consuming and risky if the equipment is mounted on an airplane or a helicopter. Therefore, they are not suitable for wide deployments and routine operations within a large-scale forest.…”
Section: Introductionmentioning
confidence: 99%
“…Radar can provide spectral information beyond vegetation cover and soil surface [12], and backscatter signals from SAR images are used to retrieve target properties, such as forest above-ground biomass, soil texture, soil moisture, and salinity. Many studies have shown that information from SAR data, such as the backscatter coefficient, can detect vegetation [64] and soil moisture [65]. There is a significant positive correlation between STN and vegetation in the topsoil [66], and the backscattering coefficient is an important indicator representing vegetation density and biomass.…”
Section: Importance Of Predictor Variablesmentioning
confidence: 99%